Preface - I. D. Mothoagae (Acta Theologica)
From text: The articles published in this issue of Acta Theologica were subjected to a rigorous blind peer review process in accordance with the required academic standard set for this journal. Authors of the African continent have contributed to this special issue that emerged partly from the Black Theology conference: “Lineages of Black Theology of Liberation and the aftermath of decolonization, post-liberation: Reflections on the present and the future” hosted by the University of South Africa, from 3 to 5 October 2012.